Aplikasi Pendukung Pelayanan Publik Berbasis Mobile Dalam Mendukung Penerapan E-Government Pada Mal Pelayanan Publik Kota Cimahi - Muhammad Rajab Fachrizal; Julian Chandra Wibawa; Rauf Fauzan; Nizar Rabbi Radliya (Majalah Ilmiah UNIKOM, 2023)
Mal Pelayanan Publik (MPP) is a facility provided by the government to integrate services from the Central Government, Regional Government, BUMN, BUMD and the private sector in one place. To improve and provide easy service to the community, MPP Cimahi City requires Information Technology support in the form of a mobile-based application. The purpose of this research is to build a mobile application as a medium that can be used by the people of Cimahi City to find out information on services available at MPP Cimahi City, make queue reservations online and track the process of submitting a service. The system development method used in this research is RAD (Rapid Application Development). While application testing is carried out through the User Acceptance Test process using the Black Box method. The results of this study are the availability of mobile-based applications that can support services for the community at MPP Cimahi City. Key Words: Mobile Application, E-Government, Mal Pelayanan Publik, RAD, Black Box